Проблема захисту українських земель від татарських нападів і становлення козацтва. (Zaporizhzhia Historical Review, 2021)
The article is devoted to the problem of defending Ukrainian lands from Tatar asaults. It proves that failures of Polish Government in organizing effective defence of Ukraine resulted in formation of Cossackhood that had assumed this function.